Assessment of Psychometric Characteristics of the Coronavirus Anxiety Scale in Patients with Preexisting Psychiatric Disorders - Karahamet, Elif; Angın, Ülkem; Yılmaz, Onat; DENİZ, DERYA; Konuk, Numan (Taylor & Francis, 2022)
This study aimed to evaluate the psychometric characteristics of the Turkish version of the CAS in a Turkish psychiatric outpatient setting. A total of 198 patients with a preexisting psychiatric disorder completed the CAS scale. The scale's validity and reliability were evaluated using convergent and concurrent validity, internal consistency, exploratory and confirmatory factor analyses, and ROC analysis. The Turkish version of CAS might help physicians assess the COVID-19 associated anxiety in patients with psychiatric comorbidities.